Мета, принципи та завдання ювенальної юстиції - Гусак, А.; Husak, A. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті проаналізовано поняття ювенальної юстиції. Її мета – не покарання як таке, а виховання молодих людей за допомогою скорочення шкідливого впливу на дітей і підлітків чинника залучення їх у кримінальне судочинство. Визначено принципи, які використовуються для пояснення ювенальної юстиції. The article examines the concept of juvenile justice. The main goal of juvenile justice is education of the young people by reducing the harmful effects on children and youths and the minimization of taking them to criminal proceedings rather than punishment. The author defines the principles and norms of juvenile justice. The main goal of juvenile justice is rehabilitation of the youths by understanding of the punishment inevitability for criminal actions. The core thesis of juvenile justice opponents is that justice takes away the juveniles from the families. It is obvious that the distinguishing mark of juvenile justice is the priority of the juvenile individual development as well as his socialization. Nowadays is the relevant time for juvenile justice administration in Ukraine. Its main goal is enforcement of juvenile civil rights on the whole (family and housing rights) as well as preventing the juvenile criminal prosecution according to the rule of law and restorative justice system.
Goals, Principles and Targets of Juvenile Justice
Keywords: ювенальна юстиція; захист дитини; виховання молодих людей; juvenile justice; juvenile protection; education of young people